Physiological and health characteristics of ex-jockeys. Issue 4 (April 2016) - Cullen, SarahJane; Donohoe, Alex; McGoldrick, Adrian; McCaffrey, Noel; Davenport, Colin; Byrne, Brendan; Donaghy, Caroline; Tormey, William; Smith, Diarmuid; Warrington, Giles
Abstract: Objectives: The long-term health implications resulting from extreme and chronic weight cycling and the associated energy restricted lifestyle of a professional jockey remain unknown. The aim of the present study was to describe and evaluate the physiological and health characteristics of retired jockeys. Design: Cross-sectional. Methods: Retired male jockeys ( n = 28; age 59 ± 6 yr; height 1.65 ± 0.03 m; body mass 73.7 ± 10.9 kg; BMI 26.9 ± 3.8 kg m −2 ) participated. Body composition (by dual energy X-ray absorptiometry; DXA), resting metabolic rate (RMR), glucose metabolism (by oral glucose tolerance test; OGTT), lipids and thyroid function were assessed. All data were interpreted in relation to established age specific reference ranges for the particular assessment undertaken. Results: Forty three percent of the retired jockeys were classified as overweight, while 21% were obese. RMR was calculated as 1447 ± 201 kcal day −1 . Mean total cholesterol was 5.93 ± 1.5 mmol L −1 for those not on cholesterol lowering medication and 5.09 ± 1.1 mmol L −1 for those currently taking medication. No abnormalities in glucose metabolism and thyroid function were found. Conclusions: Chronic weight cycling during a career as a professional jockey did not induce any health consequences in the retired jockeys assessed in this study, however enhanced weight gain and dyslipidaemia were evident. Results suggest jockeys should be tracked longitudinally throughout their racing career and beyond to further establish long-term physical health implications associated with the current lifestyle of a professional jockey.